2015
DOI: 10.1002/mds.26320
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity changes related to cognitive and motor performance in spinocerebellar ataxia type 2

Abstract: Our findings show significant correlations between functional connectivity changes in key areas affected in SCA2 and these patients' motor and neuropsychological impairments, adding an important insight to our understanding of the pathophysiology of SCA2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 65 publications
2
53
0
Order By: Relevance
“…This finding supports a cerebellar contribution to executive functions such as the ability to inhibit interfering stimuli and suggests disruptions of cerebello‐thalamic‐cortical projections,40 in line with the profound degeneration of the thalamus in SCA2 41, 42. In addition, previous studies in SCA2 patients demonstrated associations between cognitive function and brain imaging findings using voxel‐based morphometry and resting‐state functional MRI 30, 43…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This finding supports a cerebellar contribution to executive functions such as the ability to inhibit interfering stimuli and suggests disruptions of cerebello‐thalamic‐cortical projections,40 in line with the profound degeneration of the thalamus in SCA2 41, 42. In addition, previous studies in SCA2 patients demonstrated associations between cognitive function and brain imaging findings using voxel‐based morphometry and resting‐state functional MRI 30, 43…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, microstructural abnormalities measured by diffusion weighted imaging have been detected in the cerebellum and the pons28 as well as cortical alterations in SCA2 patients 10, 11, 29. Functional MRI in resting‐state modus further shows changes of cerebellar but also fronto‐ and parietal connectivity networks related to cognitive and motor performance 30, 31. No multimodal MRI data other than macroanatomical measurements exist for the preclinical stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…After initially searching, the titles and abstracts with the search strategy, eight VBM studies (Brenneis et al., 2003; D'Agata, Caroppo, Boghi et al., 2011; Goel et al., 2011; Hernandez‐Castillo et al., 2015; Jacobi et al., 2013; Mercadillo et al., 2014; Nave, Ginestroni, Tessa, Cosottini et al., 2008; Nave, Ginestroni, Tessa, Salvatore et al., 2008) were identified as potentially meeting the inclusion criteria. A detailed review of the full text was then performed, and two studies (Hernandez‐Castillo et al., 2015; Jacobi et al., 2013) were excluded due to absence of stereotactic coordinates.…”
Section: Resultsmentioning
confidence: 99%
“…Voxel‐based morphometry (VBM), a processing technique of magnetic resonance imaging (MRI) that can detect regional morphological changes in the whole brain, has been commonly used to evaluate gray matter (GM) and white matter (WM) volume abnormalities in SCA2 patients (Brenneis, Bosch, Schocke, Wenning, & Poewe, 2003; D'Agata, Caroppo, Boghi et al., 2011; Goel et al., 2011; Hernandez‐Castillo et al., 2015; Jacobi et al., 2013; Mercadillo et al., 2014; Nave, Ginestroni, Tessa, Cosottini et al., 2008; Nave, Ginestroni, Tessa, Salvatore et al., 2008; Olivito et al., 2018). However, the findings of these studies are variable and conflicting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation